2011
DOI: 10.1016/j.jcv.2011.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the optimal cut-point for HIV-p24 antigen testing to diagnose HIV infection in HIV-exposed children from resource-constrained settings

Abstract: Background-Nucleic-acid-testing (NAT) to diagnose HIV infection in children under age 18 months provides a barrier to HIV-testing in exposed children from resource-constrained settings. The ultrasensitive HIV-p24-antigen (Up24) assay is cheaper and easier to perform and is sensitive (84-98%) and specific (98-100%). The cut-point optical density (OD) selected for discriminating between positive and negative samples may need assessment due to regional differences in mother-to-child HIV-transmission rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Early diagnosis of HIV allows health care providers to offer optimal care and treatment of HIV-infected children, assists in decision-making on infant feeding, and reduces illness-related stress in mothers and families. The increasing efficacy and coverage of Prevention of Mother-to-Child Transmission of HIV (PMTCT) interventions have resulted in the majority of children born to HIV-infected mothers being HIV-free [ 5 ]. Consequently, identification of infected children before the illness is possible through routine diagnostic testing of all exposed infants.…”
Section: Introductionmentioning
confidence: 99%
“…Early diagnosis of HIV allows health care providers to offer optimal care and treatment of HIV-infected children, assists in decision-making on infant feeding, and reduces illness-related stress in mothers and families. The increasing efficacy and coverage of Prevention of Mother-to-Child Transmission of HIV (PMTCT) interventions have resulted in the majority of children born to HIV-infected mothers being HIV-free [ 5 ]. Consequently, identification of infected children before the illness is possible through routine diagnostic testing of all exposed infants.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, third generation tests have lower false-positive rates compared to fourth generation tests, suggesting that laboratory-based screening should instead be used for those at high risk of infection [137]. Tamhane et al suggested adjusting positive readout thresholds in order to optimize a modified ELISA for a given prevalence (using receiver-operator curves) but this approach would be difficult to implement in simple PoC tests [161]. Use in resource-poor settings.…”
Section: Lessons Learntmentioning
confidence: 99%
“…The Prevention of Mother-to-Child Transmission of HIV (PMTCT) program has added value to the efficiency and wide reach of interventions which has resulted in the huge number of exposed infants born without the virus [16]. Nevertheless, early detection of infants before disease strikes can be achieved through routine diagnostic checks of all exposed infants, prioritizing TAT, since prolonged TAT may result in mortality.…”
Section: Introductionmentioning
confidence: 99%